2003
DOI: 10.1007/s00216-002-1629-8
|View full text |Cite
|
Sign up to set email alerts
|

Enantiomeric purity determination of ketoprofen by capillary electrophoresis: development and validation of the method

Abstract: A simple, fast capillary electrophoresis method for determining the total ketoprofen content in an oral pharmaceutical formulation is proposed. The addition of 75 mM of heptakis(tri- O-methyl)-beta-cyclodextrin to the background electrolyte allows the quantitation of the enantiomeric impurity of ( R)-(-)-ketoprofen contained in the formulation. A relative limit of detection is proposed as a measure of the lowest detectable enantiomeric impurity and the results show that the method can detect the minor enantiom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 15 publications
2
23
0
1
Order By: Relevance
“…Different optimal conditions were found when the enantiomer impurity was situated either before or after the main compound. Determination of enantiomeric purity is mostly done under overload conditions, which leads to deformed peaks (Magnusson et al, 2002;Blanco et al, 2003), as demonstrated in Fig. 2 cases where the impurity migrates first a better and easier detection and peak integration.…”
Section: Strategymentioning
confidence: 98%
“…Different optimal conditions were found when the enantiomer impurity was situated either before or after the main compound. Determination of enantiomeric purity is mostly done under overload conditions, which leads to deformed peaks (Magnusson et al, 2002;Blanco et al, 2003), as demonstrated in Fig. 2 cases where the impurity migrates first a better and easier detection and peak integration.…”
Section: Strategymentioning
confidence: 98%
“…These include the evaluation of the synthetic process [92,94] as well as the analysis of approved drugs [81][82][83][84][85][86][87][88][89][90]. In several cases, the methods not only allowed the determination of the other enantiomer but also of related substances [84,85,92].…”
Section: Enantioseparations Of Nonracemic Mixtures Determination Of mentioning
confidence: 99%
“…Blanco and co-workers [86] developed and validated an assay for the analysis of (R)-ketoprofen in (S)-ketoprofen. The use of TM-b-CD in an acetate buffer, pH 5.0, allowed the detection of 0.04% of the (R)-enantiomer as impurity.…”
Section: Enantioseparation Of Drugs In Pharmaceutical Preparationsmentioning
confidence: 99%
“…Due to the high efficiency and a large diversity of chiral selectors available at present, CE is a powerful tool for chiral purity determinations of pharmaceuticals during different stages of drug development. Several strategies on method development [2][3][4][5][6][7] as well as validation studies [8][9][10] can be found in literature.…”
Section: Introductionmentioning
confidence: 99%